Desempenho de compósitos cimentícios fabricados com cimentos aditivados com cinzas de bagaço de cana-de-açucar in natura e beneficiadas - Paula Gisele Lamezon de Padua (2012)
The bagasse of sugarcane is usually burned for energy production and providing nearly 3% of residual ashes. The potential of these ashes into in cementitious composites will depend on the calcination conditions. The present work identifies the physical, chemical and microstructural characteristics of four types of residual ashes obtained from a controlled calcination performes in an industry located at west region of the state of Minas Gerais. Preliminary tests suggested the volatile ash is suitable as a supplementary material for cementitious composites. The volatile ashes produced during two distinct seasonal sugarcane harvests were investigated in this work. Cementitious composites were produced with 10%, 15%, 20% and 30% of ashes from the 1st harvest as pure cement substitution. The results revealed that 10% of cement replacement by ashes provides the best mechanical properties. For this reason the addition of 10% was used for further analysis including not only the ashes from the 2nd harvest, but also the ashes with physical, thermal and chemical processing. Chemical composition analysis, X-ray diffraction, grain size distribution, loss on ignition, thermogravimetry analysis, differential scanning calorimetry, specific surface measurements and Fourier Transform Infrared spectroscopy tests were used to characterize the ashes. The pozzolanic activity was estimated by pozzolanic activity index tests with cement and lime, by the modified Chapelle test, electrical conductivity in lime solution test, TGA and FTIR. Compression test, dynamic elastic modulus test, water absorption and accelerated carbonatation test were used to identify the effect of the ashes on the mechanical behavior and durability of the cementitious composites. The results showed that the ashes with high Si content and crystalline structure can be used as supplementary material when 10% of the cement is replaced. On the other hand, the ashes with low Si content and amorphous structure are not suitable for this application. The milling of the ashes not reduced the results. Laboratory calcination and chemical processing using 2% of K2SO4 of the ashes improved the porosity characteristics but the mechanical properties were not improved. The results implied that the mechanism by which the ashes affect the cementitious composite can be described as a pozzolanic reaction rather than filler effect. Moreover, the results obtained from the pozzolanic activity tests are not in accordance with the mechanical properties and durability tests.